Vulgar Superstitions: Why Elite Anglicans Stopped Believing in Witches - Rachael MacLean (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Witch persecution rose to an all-time high in England during the late sixteenth and early seventeenth centuries. However, by the turn of the eighteenth century, witch trials and witch belief had sharply declined, especially in elite circles. The accepted explanation for this historical shift has, for centuries, been that the rise of rationality, scientific reasoning, and secular humanism was incompatible with “superstitious” witch belief. Thus, the forces of enlightened thinking illuminated the ridiculousness of witches and discounted them. However, this simplistic explanation does not stand up to careful scrutiny. It contains several flawed assumptions: first, that enlightenment and post-enlightenment thinkers were definitively more rational than those in preceding time periods; second, that scientific discoveries led directly to disbelief in magic and witches; and third, that thinkers who sought to disprove the existence of witches did so through secular means. I argue that elite English disbelief in witches was caused not by new science or newly rational thought, but by a new mode of Anglican religious thought, and that this religious shift was engineered to promote a stable social order beneficial to elites.